The Regression Effect of Capital Structure and Firm Growth on the Firm value - Amin, Moh. (Golden Ratio of Finance Management, 2021)
This study aims to determine and analyze the effects of capital structure, firm growth, and profitability on the firm value on the IDX. The population in this study were all manufacturing companies in the consumer goods industry sector, as many as 42 firms, and the number of samples was as many as 12 firms using the purposive sampling method. This study uses secondary data derived from the annual financial statements of manufacturing companies listed on the IDX. The data were analyzed using SPSS program. The results of this study indicate that capital structure and profitability have a negative and insignificant effect on the firm value on the IDX. The firm's growth has a positive and negligible impact on the firm value on the IDX. Trade Off Theory explains that if the position of the capital structure is below the optimal point, any additional debt will increase the firm's value. On the other hand, if the position of the capital structure is above the optimal threshold, any additional debt will reduce the firm's value. Statistically, the capital structure has a negative and insignificant effect on the firm value in the consumer goods industry sector listed on the IDX.